Balancing short-run costs and long-run gains: The welfare implications of investing in new technologies in developing countries - Bruno de Oliveira Cruz (Instituto de Pesquisa Econômica Aplicada (IPEA), 2023)
There is long tradition in the economic literature that recognizes learning and the diffusion of new ideas and technologies as one of major drivers for growth, especially in developing countries. However, while adopting a new technology mainly involves cost, some technologies may also be human and physical specific, i.e., vintage specific. The introduction of a new capital good may require on-the-job training or fresh investment in the educational system or even physical changes on the assembly line. This paper presents an AK model with embodied capital technology, i.e., new ideas or technologies embodied in capital goods, so the country must invest so as to have access to the new technology. In order to capture these features, the paper has employed a Nelson-Phelps catch-up equation in an AK growth model. This model presents some very compelling dynamics: i) the possibility of catching-up and leapfrogging in an AK model structure; and ii) the prospect of a productivity slowdown and nonmonotonic transition toward a balanced growth path, due to the adoption cost. The optimal pace of adopting technology generates a trade-off between short-run costs and long-run benefits. These results are of particularly interest for policy makers in developing countries, given that some benefits from technology adoption may only appear after the economy learns more about the new technology. Countries may be faced with a choice, whereby the more complex the technology, the higher the short-run costs. However, the long-run gains will also be higher.
Keywords: O11; O33; O41; 330; embodied technological progress; adoption cost; learning; AK growth model